2004
DOI: 10.1038/nbt931
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme immobilization in a biomimetic silica support

Abstract: Robust immobilization techniques that preserve the activity of biomolecules have many potential applications. Silicates, primarily in the form of sol-gel composites or functionalized mesoporous silica, have been used to encapsulate a wide variety of biomolecules but the harsh conditions required for chemical synthesis limit their applicability. Silaffin polypeptides from diatoms catalyze the formation of silica in vitro at neutral pH and ambient temperature and pressure. Here we show that butyrylcholinesterase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
516
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 602 publications
(527 citation statements)
references
References 16 publications
9
516
0
2
Order By: Relevance
“…The ability of silicatein proteins to act as templates/catalysts for the biomineralization of silica has been demonstrated 36 . Numerous biomimetic synthetic silica systems have been reported and are mainly based on the modification of the protein to introduce catalytic/template sequences [36][37][38] . Here, we demonstrated that the template effect could be obtained by using a mixture of organosilanes that self-assemble around the native virus.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of silicatein proteins to act as templates/catalysts for the biomineralization of silica has been demonstrated 36 . Numerous biomimetic synthetic silica systems have been reported and are mainly based on the modification of the protein to introduce catalytic/template sequences [36][37][38] . Here, we demonstrated that the template effect could be obtained by using a mixture of organosilanes that self-assemble around the native virus.…”
Section: Resultsmentioning
confidence: 99%
“…A short time later, the synthesis of silica from a silicic acid solution 73) and the synthesis of TiO 2 from Ti-BALDH 74) were attempted using R5 peptide.…”
Section: Peptide-mediated Ceramic Synthesis and Related Techniquesmentioning
confidence: 99%
“…A matrix of spherical silica particles (typically ~500nm in diameter) is formed and provides effective encapsulation of a range of enzymes including esterases, hydrolases, peroxidases and reductases. [23,35,[56][57][58][59] The silica particles can be further integrated into flow-through systems by either: i) preparing the silica particles in batch mode and then packing them into a column or by ii) preparing the silica particles within a commercially available pre-packed column, in situ, by anchoring them to the column matrix.…”
Section: Biosilica For Imer Preparationmentioning
confidence: 99%
“…[20][21][22] Using biological molecules as scaffold templates, biomimetic silicification reactions have been shown to provide a simple and effective alternative for enzyme encapsulation. [23,24] The biologically-derived silica particles physically entrap enzymes within silica nanospheres directly as the silica particles form, providing an effective 'cage' that limits enzyme denaturation and retains high enzyme activity. The application of biologically-derived silica (biosilica) as a method for enzyme immobilization and preparation of IMERs using this method will be discussed in more detail below.…”
Section: Enzyme Immobilizationmentioning
confidence: 99%